The Agr communication system provides a benefit to the populations of Listeria monocytogenes in soil - Vivant, Anne-Laure; Garmyn, Dominique; Gal, Laurent; Piveteau, Pascal (Frontiers in Cellular and Infection Microbiology, 2014)
In this study, we investigated whether the Agr communication system of the pathogenic bacterium Listeria monocytogenes was involved in adaptation and competitiveness in soil. Alteration of the ability to communicate, either by deletion of the gene coding the response regulator AgrA (response-negative mutant) or the signal pro-peptide AgrD (signal-negative mutant), did not affect population dynamics in soil that had been sterilised but survival was altered in biotic soil suggesting that the Agr system of L. monocytogenes was involved to face the complex soil biotic environment. This was confirmed by a set of co-incubation experiments. The fitness of the response-negative mutant was lower either in the presence or absence of the parental strain but the fitness of the signal-negative mutant depended on the strain with which it was co-incubated. The survival of the signal-negative mutant was higher when co-cultured with the parental strain than when co-cultured with the response-negative mutant. These results showed that the ability to respond to Agr communication provided a benefit to listerial cells to compete. These results might also indicate that in soil, the Agr system controls private goods rather than public goods.